Using health status to measure NHS performance: Another step into the dark for the health reform in England - Valderas, J; Fitzpatrick, R; Roland, M (2012)
The National Health Service in England is moving away from targets based on processes of care and focusing on patient outcomes. This vision is operationalised in the recently published NHS Outcomes Framework, which includes the generalised use of Patient Reported Outcomes (health status and quality of life) as measures of population health at the provider level. This is the first time that such a bold initiative is attempted in the UK and it is not without risks. In this article we elaborate on our experience on the use of Patient Reported Outcomes and identify challenges and likely implications of this approach and suggest less disruptive alternatives.